Arabic Vocabulary Mastery and Its Relationship with Reading Skills (Mahārat al-Qirā’ah) Among Arabic Literature Students: Penguasaan Kosakata Bahasa Arab dan Hubungannya dengan Kemampuan Membaca (Mahārat al-Qirā’ah) di Kalangan Mahasiswa Sastra Arab - Nurtaqwa Amin; Nurjannah; Siti Nurhalisa (Language Development Center, 2026)
Background: Learning Arabic as a foreign language requires mastery of four main skills, namely listening (istimā‘), speaking (kalām), reading (qirā’ah), and writing (kitābah). Among these skills, reading skills (mahārat al-qirā’ah) play an important role in understanding academic and religious texts. However, most students in the Arabic Literature Study Program at the Indonesian Muslim University (UMI) still face obstacles in understanding Arabic texts due to their limited vocabulary (mufradāt) and weak grammatical understanding (nahwu–sharaf). Purpose: This study examines the relationship between students’ Arabic vocabulary mastery and their reading skills (mahārat al-qirā’ah) and explores the role of grammatical understanding (nahwu–sharaf) in supporting text comprehension. Method: This study employed a quantitative correlational design. Data were collected from 20 third-semester students of the Arabic Literature Study Program at UMI using a vocabulary test and a reading test. Because the population was small, total sampling (census) was applied. Data were analyzed using descriptive statistics and Pearson correlation. Results and Discussion: The results showed that 55% of students achieved grade A in vocabulary mastery, while reading skill scores were in the good category. Pearson correlation analysis revealed a strong positive relationship between vocabulary mastery and reading skills (r = 0.82; p < 0.01). Students with better mastery of nahwu–sharaf also demonstrated stronger reading comprehension. Conclusion and Implications: Vocabulary mastery was significantly associated with Arabic reading skills (r = 0.82; p < 0.01). Arabic language learning should integrate vocabulary instruction with grammatical analysis and contextual meaning so that students can comprehend texts more comprehensively.